Identification of genes regulated by histone acetylation during root development in Populus trichocarpa. (December 2016) - Ma, Xujun; Zhang, Chao; Zhang, Bing; Yang, Chuanping; Li, Shujuan
Abstract Background Histone deacetylases (HDACs) are key enzymes catalyzing the removal of acetyl groups from histones. HDACs act in concert with histone acetyltransferases (HATs) to regulate histone acetylation status, which modifies chromatin structure, affecting gene transcription and thus regulating multiple biological processes such as plant growth and development. Over a decade, certain HDACs in herbaceous plants have been deeply studied. However, functions of HDACs in woody plants are not well understood. Results Histone deacetylase specific inhibitor trichostatin A (TSA) was used to investigate the role of HDACs in organogenesis of roots and root development inPopulus trochocarpa . The adventitious roots were regenerated and grown on medium supplemented with 0, 1, and 2.5 μM TSA. TSA treatment delayed root regeneration and inhibited primary root growth. To examine the genes modified by TSA in the regenerated roots, tag-based digital gene expression (DGE) analysis was performed using Illumina HiSeqTM 2000. Approximately 4.5 million total clean tags were mapped per library. The distinct clean tags for the three libraries corresponding to 0, 1 and 2.5 μM TSA treatment were 166167, 143103 and 153507, from which 38.45 %, 31.84 % and 38.88 % were mapped unambiguously to the unigene database, respectively. Most of the tags were expressed at similar levels, showing a < 5-fold difference after 1 μM and 2.5 μM TSA treatments and the maximum fold-change of the tag copy number was around 20. The expression levels of many genes in roots were significantly altered by TSA. A total of 36 genes were up-regulated and 1368 genes were down-regulated after 1 μM TSA treatment, while 166 genes were up-regulated and 397 genes were down-regulated after 2.5 μM TSA treatment. Gene ontology (GO) and pathway analyses indicated that the differentially expressed genes were related to many kinds of molecular functions and biological processes. The genes encoding key enzymes catalyzing gibberellin biosynthesis were significantly down-regulated in the roots exposed to 2.5 μM TSA and their expression changes were validated by using real-time PCR. Conclusions HDACs were required forde novo organogenesis and normal growth of populus roots. DGE data provides the gene profiles in roots probably regulated by histone acetylation during root growth and development, which will lead to a better understanding of the mechanism controlling root development.